2022
DOI: 10.1007/s12671-022-01939-y
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Heterogeneities in Mindfulness Profiles: a Review and Latent Profile Analysis of the Five Facet Mindfulness Questionnaire Short-Form (FFMQ-SF) in the Spanish Population

Abstract: Objectives The Five Facet Mindfulness Questionnaire (FFMQ) is one of the most common self-report instruments used in scientific literature to assess mindfulness. However, mixed evidence has been provided regarding its psychometric properties. Among them, the FFMQ seems to present latent classes or profiles with specific patterns in its facets, which might explain said mixed evidence. This study explores mindfulness profiles in the Spanish population using the short form of the FFMQ (FFMQ-SF) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
(117 reference statements)
1
5
0
Order By: Relevance
“…An important aspect of the mindfulness profiles is that they differentially relate to well-being, with some profiles seemingly more adaptive than others. As might be expected, the homogeneous mindfulness profiles (i.e., high mindfulness, moderate mindfulness, low mindfulness ) tend to follow the same pattern of results as variable-centered studies ( Lecuona et al, 2022 ). That is, individuals in the high mindfulness profile have significantly greater well-being as measured by a variety of variables such as happiness, anxiety and depressive symptoms, life satisfaction, and self-regulation than those in the low mindfulness profile ( Suh et al, 2022 ; Wang et al, 2022 ; De Souza Marcovski and Miller, 2023 ).…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…An important aspect of the mindfulness profiles is that they differentially relate to well-being, with some profiles seemingly more adaptive than others. As might be expected, the homogeneous mindfulness profiles (i.e., high mindfulness, moderate mindfulness, low mindfulness ) tend to follow the same pattern of results as variable-centered studies ( Lecuona et al, 2022 ). That is, individuals in the high mindfulness profile have significantly greater well-being as measured by a variety of variables such as happiness, anxiety and depressive symptoms, life satisfaction, and self-regulation than those in the low mindfulness profile ( Suh et al, 2022 ; Wang et al, 2022 ; De Souza Marcovski and Miller, 2023 ).…”
Section: Introductionsupporting
confidence: 67%
“…Variable-centered analyses (e.g., regression, ANOVA) are largely based on mean scores that are generalized across participants to infer something about a population. Given the heterogeneous results based on mindfulness facets and across different samples in the literature, some scholars have argued that the construct should also be explored using person-centered approaches (e.g., Lilja et al, 2013 ; Pearson et al, 2015 ; Bravo et al, 2016 ; Lecuona et al, 2022 ). Person-centered analyses (e.g., cluster analyses, latent profile analyses) aim to identify subgroups within a given sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is plausible that a measure that fails to capture a general mindfulness factor driving scores on individual facets—as demonstrated by the FFMQ-15 in Study 1—is also unlikely to demonstrate moderation. In a recent study employing latent profile analysis, researchers found only 68% of respondents completing the short form of the FFMQ demonstrated a “general mindfulness” profile (Lecuona et al, 2022 ). Two other respondent profiles emerged, including a "Non-judgementally Aware” profile (24.8%), typified by a non-discerning form of awareness which does not fit a typical high mindfulness profile, and a “Judgmentally Observing” profile (7.4%).…”
Section: Discussionmentioning
confidence: 99%